Pengaruh Supply Chain Management Terhadap Kinerja Usaha Dengan Competitive Advantage Sebagai Variabel Intervening pada Restoran Kuliner Tradisional Betawi di Kecamatan Setu, Bekasi – Jawa Barat - Untari, Dhian Tyas (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of the research is to find out whether Supply Chain Management (SCM) influences the competitive advantage of Betawi Traditional Culinary Restaurants in Setu, Bekasi; to find out whether Supply Chain Management (SCM) influences business performance at Betawi Traditional Culinary Restaurants in Setu, Bekasi; to find out whether competitive advantage affects company performance at Betawi Traditional Culinary Restaurants in Setu, Bekasi; and to find out whether Supply Chain Management (SCM) influences business performance through the competitive advantage of Betawi Traditional Culinary Restaurants in Setu, Bekasi. The population in this study was Betawi Traditional Culinary Restaurants in Setu District, Bekasi. The sampling technique used in this research is a saturated sampling technique or also known as a census, which uses the entire population as a sample. What needs to be noted is that the number of traditional Betawi culinary restaurants is only 24. Data processing uses multivariate statistical methods.